Bush the transnationalist: a reappraisal of the unilateralist impulse in US foreign policy, 2001-2009 - Ryan, Maria (Palgrave Macmillan, 2017)
This article challenges the common characterisation of George W. Bush’s foreign policy as “unilateral.” It argues that the Bush administration developed a new post-9/11 understanding of terrorism as a transnational, networked phenomenon shaped by the forces of globalisation. This led to a new strategic emphasis on bi- and multilateral security co-operation and counterterrorism operations, especially outside of Afghanistan and Iraq, driven by the perceived need to counter a transnational security challenge present in multiple locations. This (flawed) attempt to engage with transnational security challenges supplemented the existing internationalist pillar of the Bush administration’s foreign policy. Highlighting the transnational realm of international relations and the ways in which the Bush administration was able to co-opt other states to tackle perceived transnational challenges also shows the high importance the administration attached to concerted action even as it frequented eschewed institutional multilateralism.